Visual conditions affecting eye growth alter diurnal levels of vitreous DOPAC. (November 2020) - Nickla, D.L.; Sarfare, S.; McGeehan, B.; Wei, W.; Elin-Calcador, J.; He, L.; Dhakal, S.; Dixon, J.; Maguire, M.G.; Stone, R.A.; Iuvone, P.M.
Abstract: In chicks, the diurnal patterns of retinal dopamine synthesis and release are associated with refractive development. To assess the within-day patterns of dopamine release, we assayed vitreal levels of DOPAC (3, 4-dihydroxyphenylacetic acid) using high performance liquid chromatography with electrochemical detection, at 4-h intervals over 24 h in eyes with experimental manipulations that change ocular growth rates. Chicks were reared under a 12 h light/12 h dark cycle; experiments began at 12 days of age. Output was assessed by modelling using the robust variance structure of Generalized Estimating Equations. Continuous spectacle lens defocus or form deprivation : One group experienced non-restricted visual input to both eyes and served as untreated "normal" controls. Three experimental cohorts underwent monocular visual alterations known to alter eye growth and refraction: wearing a diffuser, a negative lens or a positive lens. After one full day of device-wear, chicks were euthanized at 4-h intervals over 24 h (8 birds per time/condition). Brief hyperopic defocus : Chicks wore negative lenses for only 2 daily hours either in the morning (starting at ZT 0; n = 16) or mid-day (starting at ZT 4; n = 8) for 3 days. Vitreal DOPAC was assayed. In chicks with bilateral non-restricted vision, or with continuous defocus or form-deprivation, there was a diurnal variation in vitreal DOPAC levels for all eyes (p < 0.001 for each). In normal controls, DOPAC was highest during the daytime, lowest at night, and equivalent for both eyes. In experimental groups, regardless of whether experiencing a growth stimulatory input (diffuser; negative lens) or growth inhibitory input (positive lens), DOPAC levels were reduced compared both to fellow eyes and to those of normal controls (p < 0.001 for each). These diurnal variations in vitreous DOPAC levels under different visual conditions indicate a complexity for dopaminergic mechanisms in refractive development that requires further study. Highlights: DOPAC is initially reduced under all visual conditions that alter growth rate. The diurnal rhythm in DOPAC is retained under conditions altering eye growth. DOPAC is reduced during the day and the night under visual conditions altering eye growth.